EXPOSURE THERAPY FOR FLASH FLOOD DISASTER VICTIMS - Solina, Wira; Putra, Fuaddillah (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
The aftermath of the flash flood that occurred in Nagari Rambatan left trauma for the victims, the victims experienced psychological impacts where they were still worried about the subsequent flash flood disaster, then felt restless sleeping at night because they were still haunted by the incident they experienced, felt anxious and some even became stressed and traumatized. This Community Service aims to eliminate the anxiety and trauma of the flash flood victims. The method of implementing this service is by conducting observations, interviews and providing exposure therapy. The use of direct exposure therapy techniques, by facing stimuli that cause anxiety in actual conditions when they are still haunting and as if the threat of flash floods will come back. To overcome this, it can be helped using Virtual Reality (VR) head mounted display technology which can display three-dimensional images generated by a computer on each eye to display a stereo effect, thus creating an immersive or feeling of being present as an illusion in a virtual environment.